Smart sensor networks: communication, collaboration and business decision making in distributed complex environments - Hecker, Michael; Karol, A.; Stanton, C.; Williams, M. (IEEE, 2005)
Smart Sensor Networks are one of the most exciting research areas in information technology today; their potential for business applications is vast, but yet to be realised. In this paper we argue that intelligent sensor networks can only reach their potential for business applications if the network is grounded so as to support meaningful information sharing and knowledge generation as the basis for an effective business decision model. Our work is based on the idea that sensors extract information from their environment which, typically, must be fused with other sensor data and network knowledge so that effective business decision making is supported.